2013
DOI: 10.1523/jneurosci.4742-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Brain Penetrant NPS Receptor Antagonist, NCGC00185684, Blocks Alcohol-Induced ERK-Phosphorylation in the Central Amygdala and Decreases Operant Alcohol Self-Administration in Rats

Abstract: The Neuropeptide S receptor, a Gs/Gq-coupled GPCR expressed in brain regions involved in mediating drug reward, has recently emerged as a candidate therapeutic target in addictive disorders. Here, we describe the in vitro and in vivo pharmacology of a novel, selective and brain penetrant NPSR antagonist with nanomolar affinity for the NPSR, NCGC00185684. In vitro, NCGC00185684 shows biased antagonist properties, and preferentially blocks ERK-phosphorylation over intracellular cAMP or calcium responses to NPS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…In contrast, acute administration of a lower dose of EtOH (1g/kg) significantly increased pERK in various regions including the NAc, and CeA in the D1-R and neuropeptide S receptor dependent manner 236,237 . The acute EtOH-induced c-fos induction in the medial Amy was inhibited by the MEK inhibitor, U0126 238 .…”
Section: Erk Signaling and Drug Addictionmentioning
confidence: 81%
“…In contrast, acute administration of a lower dose of EtOH (1g/kg) significantly increased pERK in various regions including the NAc, and CeA in the D1-R and neuropeptide S receptor dependent manner 236,237 . The acute EtOH-induced c-fos induction in the medial Amy was inhibited by the MEK inhibitor, U0126 238 .…”
Section: Erk Signaling and Drug Addictionmentioning
confidence: 81%
“…The ERK/MAPK pathway in the central nucleus of the amygdala (CeA) is activated in response to acute ethanol injection and home cage 24-h and binge 4-h self-administration, (Ibba et al 2009; Spanos et al 2012; Thorsell et al 2013). Likewise, we found that 30 days of operant ethanol self-administration significantly increased pERK1/2 IHC in the CeA but not BLA (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…While we are aware that the total drug concentration in the brain may not be a good indicator of a pharmacodynamic effect, 33 detailed in vivo studies in rat alcohol models with 20e show efficacy with an IP dose of 1.0 mpk. 34 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we completed the evaluation of 20e in animal models of alcoholism where antagonism of NPSR is predicted to have an effect. 34 Results of these studies show a supression of alcohol self administartion in rats with a dose as low as 1 mpk. We also show that, at the same dose, 20e is able to reduce alcohol induced ERK phosphorylation in the central amygdala of these rats.…”
Section: Discussionmentioning
confidence: 97%